2017
DOI: 10.1038/nmicrobiol.2017.114
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the type IV coupling protein complex of Legionella pneumophila

Abstract: Many bacteria, including Legionella pneumophila, rely on the type IV secretion system to translocate a repertoire of effector proteins into the hosts for their survival and growth. Type IV coupling protein (T4CP) is a hexameric ATPase that links translocating substrates to the transenvelope secretion conduit. Yet, how a large number of effector proteins are selectively recruited and processed by T4CPs remains enigmatic. DotL, the T4CP of L. pneumophila, contains an ATPase domain and a C-terminal extension whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 68 publications
6
99
1
3
Order By: Relevance
“…Many VirD4 subunits also possess sequence-variable C-terminal domains (CTDs) that are typically enriched in acidic residues (Alvarez-Martinez and Christie 2009; Kwak et al 2017). When present, these CTDs also play important roles in substrate recruitment, as shown by studies of the F and pKM101 conjugation systems (see Figs.…”
Section: Function Structure and Diversification Of T4ass And T4bsssmentioning
confidence: 99%
See 2 more Smart Citations
“…Many VirD4 subunits also possess sequence-variable C-terminal domains (CTDs) that are typically enriched in acidic residues (Alvarez-Martinez and Christie 2009; Kwak et al 2017). When present, these CTDs also play important roles in substrate recruitment, as shown by studies of the F and pKM101 conjugation systems (see Figs.…”
Section: Function Structure and Diversification Of T4ass And T4bsssmentioning
confidence: 99%
“…2.2). Recently, an X-ray structure showed that DotL’s C-terminal domain (CTD) interacts with the stabilizing subunit DotN and three adaptors IcmS, IcmW, and LvgA sequentially along its length (Kwak et al 2017; Xu et al 2017). The findings underscore the importance of the CTDs of T4CPs for effector diversification and spatiotemporal control of effector presentation to the T4SS channel.…”
Section: Function Structure and Diversification Of T4ass And T4bsssmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucial for hijacking host-cell vesicles trafficking necessary for LCV biogenesis, and subsequently for intracellular multiplication of L. pneumophila, is the Type 4 Secretion System (T4SS) Icm/Dot (for Intracellular multiplication and Defect in organelle trafficking) (2, 3). The Icm/Dot system is a complex machinery located at the bacterial pole (4-6) and composed of 27 proteins involved in (i) a multiprotein apparatus for secretion (7), (ii) a coupling protein complex (DotL/IcmO; DotM/IcmP; DotN/IcmJ) (8,9) and (iii) chaperone proteins that associate with the coupling protein complex and are involved in some specific substrate recognition for presentation to the translocon (IcmS; IcmW; LvgA) (10-12). This machinery translocates an exceptionally large repertoire of effectors, over 300 proteins, into the host-cell cytosol (13).…”
Section: Significancementioning
confidence: 99%
“…Within amoeba and human macrophages, L. pneumophila evades endocytic degradation and triggers the biogenesis of a Legionella-containing vacuole (LCV), a rough endoplasmic reticulum-like compartment permissive for its intracellular multiplication (1).Crucial for hijacking host-cell vesicles trafficking necessary for LCV biogenesis, and subsequently for intracellular multiplication of L. pneumophila, is the Type 4 Secretion System (T4SS) Icm/Dot (for Intracellular multiplication and Defect in organelle trafficking) (2, 3). The Icm/Dot system is a complex machinery located at the bacterial pole (4-6) and composed of 27 proteins involved in (i) a multiprotein apparatus for secretion (7), (ii) a coupling protein complex (DotL/IcmO; DotM/IcmP; DotN/IcmJ) (8,9) and (iii) chaperone proteins that associate with the coupling protein complex and are involved in some specific substrate recognition for presentation to the translocon (IcmS; IcmW; LvgA) (10-12). This machinery translocates an exceptionally large repertoire of effectors, over 300 proteins, into the host-cell cytosol (13).Despite major progress on the Icm/Dot structure thanks to electron cryotomography technology (5,14,15), much still needs to understand the functioning of the machinery, in particular regarding the secretion control of so many effectors.…”
mentioning
confidence: 99%